TSHoma: A Rare cause of Pituitary Adenoma - Mall, D; Koirala, T; Bisht, A; Wasti, K; Nepal, R (Journal of Diabetes and Endocrinology Association of Nepal, 2024)
Background: The TSH-producing adenoma (TSHoma) prevalence in the general population is 1 to 2 cases per million, accounting for less than 2% of all pituitary adenomas. It was in 1960s where the first case of TSHoma was reported with the inappropriate secretion of TSH, could only be recognized after the introduction of the TSH RIAs. The recent development of ultrasensitive TSH assays facilitates earlier diagnosis by detecting TSH in the presence of elevated free thyroid hormones, thus ruling out primary hyperthyroidism, primarily Graves’ disease. Failure to detect the presence of TSHoma may result in dramatic consequences. This study is a review of our experience in the management of TSHoma at National academy of Medical sciences, Endocrine Unit. Here we report a 36 years old male presented with weight loss, increased frequency in stool, hand tremors and loss of libido, who was found to have TShoma in further investigation and was managed.